The Unsharable: Non-Sharing as Grief Work and Ruptures of Digital Mourning - Hjorth, Larissa; Borovica, Tamara; Gerber, Katrin (AoIR Selected Papers of Internet Research, 2026)
Social media has transformed how grief is experienced and shared, turning platforms into unexpected spaces for mourning, remembrance, and community-building. Yet grief is not only about what is made visible—it is also about what remains unseen, unspoken, and deliberately withheld. This paper explores non-sharing as grief work, examining the ruptures that emerge when mourning does not align with platform logics of visibility, algorithmic curation, or public engagement. While digital mourning is often framed as a means of connection, we highlight how grief may be disrupted by grief policing, moderation practices, and the pressure to conform to platformed expressions of loss. Drawing on interviews with bereaved individuals and professionals, we introduce grief ruptures—breaks in digital continuity where the complexities of mourning exceed platform affordances. These ruptures surface in content moderation that obscure certain losses, self-censorship of stigmatized grief, and tensions between personal grieving and public sharing. This paper argues that non-sharing is not a void but a meaningful refusal, challenging dominant narratives of digital mourning as inherently visible. For internet researchers, these ruptures raise methodological questions about how to study the unseen. Traditional digital ethnography may prioritize what is publicly posted, yet grief often manifests through absence, withdrawal, and refusal. We propose new approaches that account for non-use, silence, and platform resistance, contributing to broader discussions on platformisation, grief literacies, and the evolving politics of loss in digital spaces.